2002
DOI: 10.1093/humrep/17.12.3046
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic changes of granulocyte colony-stimulating factor (G-CSF) mRNA in the human follicle during the normal menstrual cycle and immunolocalization of G-CSF protein

Abstract: These results demonstrate that G-CSF is produced in the human follicle shortly before the ovulatory phase and may play an important role in the mechanism of ovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Ovulation has several similarities with inflammation and is closely connected to the activity of leukocytes and inflammatory cytokines. G-CSF is produced in the human follicle shortly before the ovulatory phase and may play an important role in the mechanism of ovulation (Makinoda et al 1995, Yanagi et al 2002. It is likely that the constitutive overexpression of G-CSF may destroy a finely tuned mechanism of ovulation.…”
Section: Granulocyte-colony Stimulating Factormentioning
confidence: 99%
“…Ovulation has several similarities with inflammation and is closely connected to the activity of leukocytes and inflammatory cytokines. G-CSF is produced in the human follicle shortly before the ovulatory phase and may play an important role in the mechanism of ovulation (Makinoda et al 1995, Yanagi et al 2002. It is likely that the constitutive overexpression of G-CSF may destroy a finely tuned mechanism of ovulation.…”
Section: Granulocyte-colony Stimulating Factormentioning
confidence: 99%
“…These results are comparable other studies as they showed WBCs start rising from 8th day onwards 3,9 , some showed similar results but not significant 2 . One of the underlying mechanism could be that a 10 times increased production of Granulocyte colony stimulating factor (G-CSF) from the follicular cells of ovarian follicles specially at late follicular phase which might have increased the WBC count in proliferative phase 10,11 . As there are studies which have mentioned that estrogen could be the reason for increased WBC as it increases the granulocyte proliferation 6,9 , inhibits the apoptosis of granulocytes (functions of neutrophils will be intact in spite of delayed apoptosis) 12 , in different clinical scenario like as a treatment for prostatic cancer in males 13,14 , others like Hormonal replacement therapy(HRT) in case of postmenopausal women there was increased in total WBC count 15,16 .…”
Section: Among Women There Is a Physiological Variation Of Total Wbc mentioning
confidence: 99%
“…The use of BMI perpetuates the myth that excess weight is the prime concern when the true concern is excess body fat, especially around the abdominal area. Several studies have demonstrated that the WC is superior to BMI as a risk marker (2,3 ). Some studies have indicated that peripheral body fat is negatively associated with indicators of insulin resistance, whereas central body fat is positively associated with insulin resistance (4 ).…”
Section: To the Editormentioning
confidence: 99%
“…In his zeal to champion the virtues of measuring WC, Dr. Lear seems to have overlooked the overall thrust of my comments concerning the relationship between obesity, insulin resistance, and the ATP III criteria for identifying the metabolic syndrome. The major point I tried to make was that obesity (no matter how it is measured) is not a consequence of insulin resistance, but simply makes it more likely that a person will be insulin resistant and that a substantial number of obese individuals are neither insulin resistant nor at increased risk of cardiovascular disease (2)(3)(4)(5). Indeed, it is likely that differences in degree of fitness are as powerful as variations in adiposity in modulation of insulin action (2 ).…”
Section: Dr Reaven Respondsmentioning
confidence: 99%